2016
DOI: 10.1111/aos.12959
|View full text |Cite
|
Sign up to set email alerts
|

Electrolyte composition of retro‐oil fluid and silicone oil‐related visual loss

Abstract: ABSTRACT.Purpose: Up to one-third of patients with intra-ocular silicone oil (SO) tamponade for complex macula-on retinal detachment may experience an unexplained visual loss during or after SO tamponade. Although the underlying mechanism is unknown, previous studies suggested that accumulation of retinal potassium could be involved. Hence, this study tested the hypothesis that intraocular potassium levels are elevated during SO tamponade. Methods: A prospective cohort study was carried out from 13 October 201… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
22
1
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 20 publications
3
22
1
2
Order By: Relevance
“…Therefore, the hypothesis of potassium siphoning failure as a mechanism of unexplained visual loss after SO use or removal might in our opinion be a subject of controversy. This is in agreement with Scheerlinck et al [19] , who lately found that potassium and sodium levels were not increased in retro-oil fluid during SO tamponade, while magnesium and chloride levels were significantly lower in retro-oil fluid compared with vitreous humor, and lactate dehydrogenase levels were highly significantly elevated in retro-oil fluid.…”
Section: Color Version Available Onlinesupporting
confidence: 92%
“…Therefore, the hypothesis of potassium siphoning failure as a mechanism of unexplained visual loss after SO use or removal might in our opinion be a subject of controversy. This is in agreement with Scheerlinck et al [19] , who lately found that potassium and sodium levels were not increased in retro-oil fluid during SO tamponade, while magnesium and chloride levels were significantly lower in retro-oil fluid compared with vitreous humor, and lactate dehydrogenase levels were highly significantly elevated in retro-oil fluid.…”
Section: Color Version Available Onlinesupporting
confidence: 92%
“…Once the SO is removed, the K + concentration undergoes sudden changes that activate apoptosis through caspase-3 and caspase-9 pathways [34]. However a recent study found that the potassium levels are not increased in retro-oil fluid during silicone oil tamponade rendering this hypothesis unlikely [37]. …”
Section: Discussionmentioning
confidence: 99%
“…Previously, we showed that microperimetry is a sensitive test to demonstrate a deep central scotoma in eyes with SORVL (Scheerlinck et al. ,b). We also noted that the central scotoma on microperimetry in SORVL is different from the microperimetry pattern seen in eyes with a macula‐off RRD with similar visual acuity (VA) (Scheerlinck et al.…”
Section: Introductionmentioning
confidence: 90%
“…; Scheerlinck et al. ,b). Silicone oil‐related visual loss (SORVL) is characterized by a profound and irreversible visual loss occurring during SO tamponade or shortly after SO removal, without abnormalities on optical coherence tomography (OCT) or fluorescein angiography (Newsom et al.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation